No association of promoter variations of HMOX1 and UGT1A1 genes with liver injury in chronic hepatitis C - Urbánek, Petr; Leníček, Martin; Muchová, Lucie; Subhanová, Iva; Dušek, Ladislav; Kaspříková, Nikola; Hrabal, Petr; Bruha, Radan; Vítek, Libor (Annals of hepatology, 2011)
BACKGROUND: Heme oxygenase-1 (HMOX1) and bilirubin UDP-glucuronosyltransferase (UGT1A1), both enzymes involved in bilirubin homeostasis, play an important role in oxidative stress defense. OBJECTIVE: To assess the effect of promoter variations of HMOX1 and UGT1A1 genes on the progression of fibrosis in patients chronically infected with the hepatitis C virus (HCV). MATERIAL AND METHODS: The study was performed on146 chronic HCV infection patients, plus 146 age- and sex-matched healthy subjects. The (GT)n and (TA)n dinucleotide variations in HMOX1 and UGT1A1 gene promoters, respectively, were determined by fragment analysis in all subjects. RESULTS: No differences were found in the frequencies of each particular allele of both genes, between HCV patients and a control group (p > 0.05). Furthermore, no association was detected (p > 0.05) between either the HMOX1 or the UGT1A1 promoter variants and the individual histological stages of liver disease in the HCV positive patients. Finally, no differences in the HMOX1 and UGT1A1 genotype prevalence rates were found between pre-cirrhotic and cirrhotic patients (p > 0.05). CONCLUSION: Based on our data, microsatellite variations in the HMOX1 and UGT1A1 genes are not likely to protect from progression of liver disease in patients with chronic hepatitis C.
Keywords: Genetic Predisposition to Disease; Liver; Hepatitis C, Chronic; játra; glukuronosyltransferasa; Viral Load; Heme Oxygenase-1; chronická hepatitida C; mikrosatelitní repetice; Česká republika; jaterní cirhóza; Promoter Regions, Genetic; Liver Cirrhosis; Biopsy; studie případů a kontrol; genetická variace; RNA, Viral; fenotyp; Microsatellite Repeats; Czech Republic; Glucuronosyltransferase; hemoxygenasa-1; Genetic Variation; Phenotype; Humans; frekvence genu; virová nálož; promotorové oblasti (genetika); biopsie; Gene Frequency; Case-Control Studies; genetická predispozice k nemoci; RNA virová; lidé; Hepacivirus